Perlindungan Hukum Terhadap Hak Cipta atas Batik Di Kota Serang Provinsi Banten - Sulasno Sulasno; Mia Mukaromah (Ajudikasi : Jurnal Ilmu Hukum, 2019)
This writing aims to find out how the legal protection of the copyright of batik in the city of Serang with the provisions contained in Law No. 28 of 2014 concerning Copyright and regional regulations governing the protection of copyright in the city of Serang.But now researchers have not found any specific regional regulations governing Copyright (Batik Art) in Serang City. Batik is one of the works of art that requires high intellectuals in its creation. Legal protection of batik copyrights is needed to avoid things that will harm the creator and the copyright holder. The method used is the empirical normative legal research method, namely the incorporation of normative legal provisions (laws) with empirical elements (legal events in society / social elements).